The Role of Mental Models in Addressing Academic Anxiety in Children - Novianti Retno Utami; Windy Wulandari Iman Utama (Journal of Early Childhood Education Research, 2025)
Purpose: Academic anxiety is a prevalent psychological challenge that negatively affects children’s academic performance and emotional well-being. Mental models, understood as cognitive–emotional frameworks encompassing executive function and emotional regulation, play a critical role in how children perceive, interpret, and manage academic stress. This study aims to synthesize empirical evidence on the role of mental models in addressing academic anxiety in children and to identify effective school-based strategies that support adaptive learning and well-being. Methodology: This study employed a narrative review approach with a systematic search strategy. Peer-reviewed empirical studies published between 2015 and 2025 were identified through major academic databases, including Scopus-indexed journals, PubMed, and Google Scholar. The review focused on studies examining academic anxiety, executive function, emotional regulation, and school-based interventions in children and early adolescents. Relevant findings were analyzed and synthesized thematically to identify consistent patterns and key mechanisms. Results: The thematic synthesis indicates that academic anxiety is consistently associated with impairments in executive function, emotional regulation, and academic engagement. Deficits in planning, organization, attentional control, and impulse regulation were frequently identified as mediating factors linking anxiety to poorer academic outcomes. Furthermore, school-based interventions—particularly cognitive-behavioral programs, mindfulness-based approaches, holistic stress management, and emotional intelligence training demonstrated effectiveness in reducing anxiety symptoms while simultaneously improving academic performance and psychosocial adjustment. Conclusions: Mental models constitute a central mechanism through which children experience and cope with academic anxiety. Strengthening executive function and emotional regulation as core components of these mental models is essential for mitigating academic anxiety and promoting educational success. The findings underscore the importance of integrating evidence-based, multifaceted interventions into school systems to support children’s cognitive, emotional, and academic development.